Perubahan Musik Calung Punklung Menuju Musik Modern (Parakan Muncang-Kabupaten Sumedang Tahun 2003-2010) - Fadillah, Riyanti Nurina; Isana, Widiati (Historia Madania: Jurnal Ilmu Sejarah, 2020)
Calung art is one of the original arts typical of the West Java region and has existed since ancient times, and is commonly used during traditional ceremonies such as traditional ceremonies offered to Dewi Sri or better known as traditional ceremonies "seren taun". In this traditional ceremony the calung art became one of the supporting musical instruments played in the ceremonial process. However, it cannot be denied that this era which is increasingly developing into modern day more or less makes the existence of this calung experience a shift. This study aims to determine how the history of Calung Punklung's music and the process of its change to modern music. The research method used in this study is a qualitative method by collecting sources of literature coupled with sources of interviews and documentation. The analysis technique used is by using heuristic methods, criticism, interpretation and historiography. The results of this study show that the presence of the Calung Punklung music group is an effort to preserve Sundanese culture in the arts in particular. As for the changes made by the Punklung Clung group, this has only just happened in the aspect of bringing the genre of the song that was sung and how to dress when the performance.